The Examining Tourist Push-pull Motivation on Revisit Intention in Banyuwangi Tourism Destination - Cardias, Esa Riandy; Ratri, Indira Nuansa; Ermawati, Eka Afrida; Putra, Adetiya Prananda (KnE Social Sciences, 2024)
The motivation of tourists to travel can be changed by various factors. One of which is the pandemic that occurred 1 year ago. The pandemic is likely affect or even chang the pattern of tourist motivation in determining their tourist destinations. Analysis related to motivation is increasingly important when it is related to tourism as a phenomenon of the world community, where tourist behavior is influenced by various motivations when going on a trip. This research aims to analyze the motivation of push and pull tourists toward the revisit intention in Banyuwangi destination. The respondents of this research were 100 foreign tourists. Data were analyzed using a quantitative approach obtained through surveys with questionnaires as the main research instrument. The analytical tool used to confirm the model of tourist motivation on revisit intention is PLS-PM structural model analysis. The findings of this research show that five push factors of foreign tourist motivation do not affect tourist revisit intention. Those factors are adventure motivation, culture experience motivation, escape motivation, noveltyseeking motivation, and social contact motivation. The pull factors of attractiveness motivation and infrastructure motivation have a significant positive effect on revisit intention. Meanwhile, facilities motivation has no effect on revisiting foreign tourists in Banyuwangi Destination. Keywords: push factors, pull factors, tourist motivation, revisit intention, partial least square, Banyuwangi